Effect Tunneling Incentive, Intangible Assets, Profitability on Transfer Pricing Moderation Tax Avoidance - Rio Johan Putra; Amalia Astiani Rizkillah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to provide empirical evidence regarding the effect of tunneling incentive, intangible assets, profitability on transfer pricing with tax avoidance as moderating in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sample used in this study is 10 companies in the food and beverage sub-sector for the period 2016-2020. This study shows that tunneling incentives have an effect on transfer pricing, intangible assets have no effect on transfer pricing, and profitability has an influence on transfer pricing and tax avoidance has no effect on transfer pricing. Then the tax avoidance is not able to moderate the effect of tunneling incentives, intangible assets, profitability on transfer pricing.